Where is the (ancient) ocean floor? - Maric, Filip; Poto, Margherita; Panieri, Giuliana (Septentrio Educational, 2023)
Focus: To understand that that the ocean floor is dynamic and changes through time. Sometimes it’s far away, and sometimes much closer than we think. But where is the ocean floor? Learning objectives: In this activity, pupils will understand that we can find ancient ocean floors on land because of tectonic activity. NB: This will require prior planning and may not be possible if your school is too far from such tectonic formations. Key words: Sedimentation, sedimentary rocks, tectonics, Earth history.